Science & spirituality: an Islamic perspective - Abdul Razak, Mohd Abbas; Abdul Razak, Abdul Latif; Ali Zaroum, Abdulhamid Mohamed (2018)
This presentation explains on how issues related to science and spirituality are viewed from the Western and Islamic perspectives. Besides, explaining the advantage and disadvantage of modern science, the presentation also entertains some discussion on the diversity of the human intelligence. In realizing the downside of modern science and how it has been used for destructive purposes, the researchers recommend on how science can be employed in a positive manner that can yield good results for the benefit of mankind. Moreover, they highlighted that large parts of modern science are in harmony with the Islamic principles. The parts rejected by Islam are those ideas of modern science that go against the fundamental teachings of the religion, like designer babies, sperm bank, human cloning, creation of nuclear bombs, chemical weapons, biological warfare, etc.